2002
DOI: 10.1073/pnas.202335899
|View full text |Cite
|
Sign up to set email alerts
|

Functional coadaptation between cytochrome c and cytochrome c oxidase within allopatric populations of a marine copepod

Abstract: Geographically isolated populations may accumulate alleles that function well on their own genetic backgrounds but poorly on the genetic backgrounds of other populations. Consequently, interpopulation hybridization may produce offspring of low fitness as a result of incompatibilities arising in allopatry. Genes participating in these epistatic incompatibility systems remain largely unknown. In fact, despite the widely recognized importance of epistatic interactions among gene products, few data directly addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(170 citation statements)
references
References 30 publications
5
164
1
Order By: Relevance
“…Moreover, classic experiments demonstrated that simple genetic incompatibilities underlie hybrid inviability between Crepis species and cause the ''Corky'' syndrome of Gossypium species hybrids (Hollingshead 1930;Stephens1946). Similarly, in Tigriopus californicus, enzymatic activity of two interacting proteins, cytochrome c oxidase and cytochrome c, is reduced when they come from different populations (Rawson and Burton 2002), which might cause hybrid fitness problems (Willett and Burton 2001). In Xiphophorus, a simple two-locus incompatibility causes malignant tumor formation in species hybrids (Wittbrodt et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, classic experiments demonstrated that simple genetic incompatibilities underlie hybrid inviability between Crepis species and cause the ''Corky'' syndrome of Gossypium species hybrids (Hollingshead 1930;Stephens1946). Similarly, in Tigriopus californicus, enzymatic activity of two interacting proteins, cytochrome c oxidase and cytochrome c, is reduced when they come from different populations (Rawson and Burton 2002), which might cause hybrid fitness problems (Willett and Burton 2001). In Xiphophorus, a simple two-locus incompatibility causes malignant tumor formation in species hybrids (Wittbrodt et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear-mitochondrial coadaptation: The coadaptation hypothesis predicts that disrupted mitonuclear genotypes (e.g., Dmel nuclear chromosomes with Dsim mtDNA) should have reduced performance, and there is compelling evidence for this in a variety of systems (Edmands and Burton 1999;Rawson and Burton 2002;McKenzie et al 2003;Sackton et al 2003). It might follow that such genotypes would have reduced longevity due to disrupted OXPHOS functions, possibly resulting in elevated ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…This has been most prominently illustrated by observations of intergenomic incompatibilities leading to mitochondrial dysfunction following experimental hybridization in the marine copepod, Tigriopus californicus. Such hybridization results in fitness breakdown in the F 2 generation, marked by decreased survivorship of larvae [62], slower development [63], reduced fecundity and viability [64], as well as decreased cyclooxygenase (COX) activity and ATP production [64][65][66]. The decrease in COX activity and ATP production is plausibly triggered by a set of mutations in the mitochondrial cytochrome c [67,68].…”
Section: Interpopulation Interactionsmentioning
confidence: 99%